Depression, anxiety and stress, during COVID-19 pandemic among midwives in ethiopia: A nationwide cross-sectional survey - Kassahun, Eskeziaw Abebe; Kassie, Belayneh Ayanaw; Tilahun, Sewbesew Yitayih; Bizuneh, Asmamaw Demis (Frontiers in Psychiatry, 2022)
Background: Coronavirus disease (COVID-19) has rapidly crossed borders, and causes anxiety and fear. Midwives were a frontline healthworkers providing care for women during COVID-19 pandemic period. Midwives who come close in contact with women when providing care are often left stricken with inadequate protections from contamination causing fear, anxiety, and depression Therefore, this study aimed to assess the level of depression, anxiety and stress among midwives in Ethiopia. Methods: Quantitative cross-sectional study was conducted from June 20 to August 20, 2020, among 1,691 midwives who worked in clinical practice in Ethiopia. Simple random sampling technique was used to select study participants. A pretested and structured questionnaire was used to collect data through telephone interview. Data was entered using the Google forms platform and analyzed with SPSS version 25. Both bivariate and multivariable logistic regression analyses were employed. Adjusted Odds Ratio (AOR) with 95% confidence interval was used to determine independent predictors of Depression, Anxiety and Stress. Results: The prevalence of depression, anxiety and stress among midwives in Ethiopia were 41.1% (95% CI: 38.6, 43.7), 29.6% (95%CI: 27.3, 31.8) and 19.0% (95% CI: 17.0, 20.8) respectively. The sex of midwives (AOR=1.35; 95%CI: 1.08,1.69), working in rural area (AOR=1.39; 95%CI: 1.06,1.82), poor knowledge of COVID-19 (AOR=1.40; 95% CI: 1.12,1.75), poor preventive practice (AOR=1.83; 95% CI: 1.47,2.28) and substance use (AOR=0.31; 95%CI: 0.17,0.56) were significantly associated with depression. Working in governmental health facility (AOR=2.44; 95%CI: 1.24,4.78), poor preventive practice (AOR=1,47; 95%CI: 1.16,1.85) and poor attitude towards COVID-19 (AOR=2.22; 95%CI: 1.04,1.66) were significantly associated with anxiety. Stress were affected by working in rural area (AOR=0.57; 95% CI: 0.39, 0.83), substance use (AOR=2.06; 95% CI: 1.51, 2.81), poor knowledge towards COVID-19 (AOR=1.44; 95% CI: 1.20, 1.90) and poor preventive practice towards COVID-19 (AOR=1.60; 95% CI :1.23, 2.10). Conclusion: Addressing knowledge and preventive practice gaps through information, training and safety protocols on COVID-19 modes of transmission, and prevention related precaution is essential to preserve the mental health of Midwives during the COVID-19 pandemic